STUDY OF GEORTONYMS IN RUSSIAN LINGUISTICS (Scientific journal of the Fergana State University, 2024)
This article analyzes the field of onomastics and georonyms, which are an important source of its current research. This article presents in-depth studies of georthonymic units by Russian linguists.